EFEKTIVITAS PEMBELAJARAN DENGAN MENGGUNAKAN LEMBAR AKTIVITAS SISWA (LAS) MATEMATIKA KELAS X SMA BERBASIS VARIASI MODEL PEMBELAJARAN KOOPERATIF - Tetty Natalia Sipayung; Sinta Dameria Simanjuntak (Universitas Sultan Ageng Tirtayasa, 2018)
ABSTRACTThis study aims to determine: (1). the validity of student mathematics worksheet for tenth grade of Senior High School based on variation of cooperative learning model and, (2) the effectiveness of learning using student mathematics worksheet for tenth grade of Senior High School based on variation of cooperative learning model. This research is a quantitative research with descriptive method that describe the effectiveness of learning by using student mathematics worksheet based on variation of cooperative learning model. The population of this study is all students of grade X SMA Nusantara Lubuk Pakam. While the sample of this study are class X MIA-1, X MIA-4, X IPS-2 and X IPS-3. XMIA-1 class as experimental class that is taught by using student mathematics worksheet based on variation of cooperative learning model. While class X MIA-4, X IPS-2, and X IPS-3 are control classes that are taught without using student mathematics worksheet and apply conventional learning. The result of this research are (1) student mathematics worksheet for tenth grade of Senior High School based on variation of cooperative learning model is valid; (2) learning using student mathematics worksheet for tenth grade of Senior High School based on variation of cooperative learning model is effective. It is analyzed based on student activity and learning outcomes in the experimental class and in the control class. Keywords: Student Worksheet, Cooperative Learning Model